Charge Carrier Mobility: Unraveling Unprecedented Charge Carrier Mobility through Structure Property Relationship of Four Isomers of Didodecyl[1]benzothieno[3, 2‐b][1]benzothiophene (Adv. Mater. 33/2016). Issue 33 (September 2016) - Tsutsui, Yusuke; Schweicher, Guillaume; Chattopadhyay, Basab; Sakurai, Tsuneaki; Arlin, Jean‐Baptiste; Ruzié, Christian; Aliev, Almaz; Ciesielski, Artur; Colella, Silvia; Kennedy, Alan R.; Lemaur, Vincent; Olivier, Yoann; et al.
Abstract : Could molecular semiconductors one day compete with their inorganic counterparts? On page 7106, S. Seki, Y. H. Geerts and co‐workers unravel, by field‐induced time‐resolved microwave conductivity measurements, an unprecedentedly high average interfacial mobility of 170 cm 2 V −1 s −1 for 2, 7‐didodecyl[1]benzothieno[3, 2‐b][1]benzothiophene over short length‐ and time‐scales. Approaching for the first time the hole mobility in single‐crystalline silicon, these results hold great promise for the field of organic electronics.